A8 REPEATED SUBMERGENCE OF AIR-LIQUID INTERFACE COLONOID CULTURES IMPAIRS INFLAMMATORY AND REGENERATIVE RESPONSES. (21st February 2022) - Rees, W D; Telkar, N; Lin, D; Wong, M; Poloni, C; Fathi, A; Kobor, M; Zachos, N; Ted, S
Abstract: Background: Damage in the intestinal epithelium is repaired via de-differentiation of mature intestinal epithelial cells to a stem-like state. Indeed, literature has primarily focused on acute forms of intestinal damage, but there is a lack of models to study how intestinal stem cells function after chronic injury, such as in inflammatory bowel disease (IBD). A previous report found that growth of mouse intestinal organoids in air-liquid interface (ALI) follows by submergence caused differentiation and reversible injury, but this has not been demonstrated in human cells or with repeated cycles of injury. Understanding how chronic damage alters human intestinal stem cell fate and function is imperative to developing novel therapies that repair the epithelium in people with IBD Aims: To develop a robust in vitro model to differentiate and damage human intestinal epithelial cells, with or without the addition of bacterial flagellin to mimic pathogen exposure. Methods: Human colonoid monolayers were seeded on Transwell inserts for 10 days until fully confluent and then differentiated by removing the apical media to create ALI growth conditions for 7 days. To induce damage, media was added to the apical side of the Transwell, with or without the addition of flagellin in the basolateral compartment. Following submergence induced damage, the apical media was removed and collected for chemokine analysis, and the cells were grown back in ALI for 3 days to recover them from injury. This cycle was repeated 5 times to induce chronic damage. Cells were collected for qPCR analysis, immunofluorescence imaging, RNA sequencing and DNA methylation analysis Results: Repeated rounds of damage impaired the ability of intestinal epithelial cells (IECs) to respond to TLR stimulation (a decrease in basolateral IL-8 with each round), likely due to a decrease in TLR signaling pathways, as demonstrated by GSEA and qPCR. Chronic submergence damage led to an increase in differentiation of cells expressing MUC2, SLC26a3 and CHGA, and a decrease in stemness as shown by qPCR for BMI1, HOPX, and LGR5. After several rounds of damage, colonoid monolayers were unable to regrow as monolayers after passaging, likely due to a decrease in YAP signaling. We also identified mRNA expression and DNA methylation changes in genes associated with IBD and colon cancer. Conclusions: We have developed a novel chronic damage model of recurrent IEC injury, which possibly mimics pathologies seen in people with inflammatory bowel disease. This model can be used to understand how chronic damage alters the ability of IECs to respond to pathogens and regenerate to repair and protect the epithelium from further damage. Funding Agencies: CCC